A linear algorithm for conformal 3D-to-flatness coordinates conversion. Issue 1 (2nd January 2017) - Shulunov, Vyacheslav; Esheeva, Irina
ABSTRACT: Data conversion from a 3D raster to spiral coordinates is the key function in the scanning process for Roll Powder Sintering (RPS) additive manufacturing technology. Conversion process is especially important, as it produces the basis for a processed object. There are many equations for such conformal transformation, but there is still room to improve the computation efficiency. This paper presents an efficient conversion algorithm, which processes 3D objects and linear transforming it into rolling ribbon. The new algorithm has several significant advantages over the old ones due to applying only one main linear equation. The program based on the linear algorithm is simpler, more compact and faster in comparison to other programs which use trigonometric, transcendental or other equations. The proposed algorithm has been developed and extensively tested on several parts of computer-aided design models for RPS processing.